Productivity analysis using objective matrix method - Evo Pradiatama (Universitas Negeri Padang, 2021)
PT. Perkebunan Nusantara VI Kayu Aro Business Unit produces tea in accordance with the amount specified in the Production Budget Work Plan (RKAP). However, the production plans that have been prepared in the company's RKAP are not always fulfilled. PT. Perkebunan Nusantara VI Kayu Aro has an annual production target, this is done to measure the level of success in achieving production at the end of the year, but in practice there is a mismatch between the targets set and the final results obtained. The results of the overall productivity measurement from January 2018 to December 2019 were 682.188, respectively; 580,654; 624,530; 441,858; 469,400; 410.946; 587,024; 642,296; 389,932; 292,519; 315,789; 618,904; 556,923; 568,097; 578,432; 456,378; 573,192; 578,432; 477,372; 505.441; 207,577; 497,522; 542.492; and 354.165